Analisis Metode dan Pendekatan Dakwah dalam Film Buya Hamka Volume 1 - Muhammad Ramdhan Alghifari; Fahmi Irfan; Falizar Rivani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Film is a modern communication medium that is effective for entertaining and conveying messages that can influence attitudes, thought patterns and open insight for the audience. In every film made, the film maker has his own way of conveying messages to the audience with audio and visuals. Nationalist documentary genre films can increase the audience's spirit of nationalism. Nationalism is very important because nationalism is a national spirit that absolutely must exist in every individual as a citizen of the Indonesian nation. The aims of this research are: 1) To examine the da'wah approach in the Buya Hamka film volume 1, 2) To analyze the da'wah methods used by buya hamka in the film buya hamka volume 1. The type of research used is qualitative with a descriptive approach. Data collection used observation techniques, interviews, by interviewing 5 viewers of the Buya Hamka film volume 1 and verifying the data using triangulation and documentation. The research results show that the da'wah method in the film Buya Hamka is the da'wah method used in the film, such as lecture, dialogue, or characterization methods that represent Islamic values. The importance of including preaching values in films effectively and interestingly without reducing the entertainment value of the film. The da'wah approach in the Buya Hamka film discusses the da'wah approach applied by Buya Hamka, for example whether the approach used is more humanistic, persuasive, or intellectual, in order to be able to convey religious values relevantly in the socio-cultural context of the society depicted in the film. This also needs to be included.